2022
DOI: 10.5005/jp-journals-10071-23991
|View full text |Cite
|
Sign up to set email alerts
|

Direct Medical Cost Analysis of Indian COVID-19 Patients Requiring Critical Care Admission

Abstract: A bstract Introduction Intensive care unit (ICU) admission is required for approximately 25% of patients affected with coronavirus disease-19 (COVID-19) and imposes a high economic burden on patients in resource-limited settings. Method We conducted a retrospective direct medical care cost analysis of COVID-19 patients requiring ICU admission after obtaining the Institutional Ethics Committee approval. Data were obtained from the records of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…and reported [10,[26][27][28]. In studies where the total cost was reported for all patients, the cost per person was calculated using the number of people who used the service [29].…”
Section: Plos Onementioning
confidence: 99%
“…and reported [10,[26][27][28]. In studies where the total cost was reported for all patients, the cost per person was calculated using the number of people who used the service [29].…”
Section: Plos Onementioning
confidence: 99%
“…Summing up, most of the studies considered here (nine articles) only focus on the analysis of direct costs and take into consideration economic costs related to hospitalization, RT-PCR for SARS-CoV-2, ICU stay, or chest radiograph, among others. Only four articles examine other types of costs or several types of costs at the same time, such as indirect costs, including those associated with the cost of missed workdays (patients as well as 19 Tsai et al 20 ), Asia (Khan et al; 21 Lee et al; 22 Li et al; 23 Reddy et al; 24 Ebrahimipour et al; 25 Darab et al; 26 Jin et al; 27 Nakhaei et al 28 ), and Europe (Romeyke and Stummer 16 ; Carrera-Hueso et al; 29 Maltezou et al 30 ). Note 2-Countries by area: America (United States), Asia (Saudi Arabi, Korea, China, Iran, and India), and Europe (Spain, Greece, and Germany).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that around 70% of the sample (exactly, 69.23% of them) only focused on direct costs. Besides, regarding country information, it is obtained for America (United States), Asia (Saudi Arabi, Korea, China, Iran, and India) and Europe (Spain, Greece, and Germany) being their corresponding references for each area the following: America (Di Fusco et al; 19 Tsai et al 20 ), Asia (Khan et al; 21 Lee et al; 22 Li et al; 23 Reddy et al; 24 Ebrahimipour et al; 25 Darab et al; 26 Jin et al; 27 Nakhaei et al 28 ), and Europe (Romeyke and Stummer 16 ; Carrera-Hueso et al; 29 Maltezou et al 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 49 Moreover, catastrophic health expenses due to severe illness leading to impoverishment or bankruptcy have been reported in India, the US, and China. 50 , 51 Decisions regarding withholding and withdrawing therapy are often challenging, and the study suggests that withholding therapy or non-escalation of therapy is more accessible than withdrawing therapy, especially the ventilator. Withdrawal of therapy is less common in the Indian (and Asian) setting as compared to the West.…”
Section: Discussionmentioning
confidence: 99%